Romantic ecocriticism : origins and legacies - Hall, Dewey W. (Ecocritical theory and practice., 2016)
Romantic Ecocriticism: Origins and Legacies examines the influence of the science of the age upon a host of English and American authors. The collection of essays develops transhistorical and transnational perspectives to examine the invaluable place of Romantic literary studies as inspiration behind the rise of early environmentalism in the nineteenth century and its subsequent legacies.